Strategi Penyuluhan Pekarangan Pangan Lestari Mendukung Kemandirian Pangan di Kecamatan Kedamean Kabupaten Gresik - Ilmi, Alvin Miftakhul; Jumadi, Rahmad; Djazuli, Raden Achmad (CV.ITTC INDONESIA, 2025)
This study aims to identify the potentials and problems of home garden utilization, analyze extension and assistance strategies, and formulate policy recommendations for the development of the Sustainable Home Food Garden Program in supporting food self-sufficiency in Kedamean Sub-district, Gresik Regency. The methods used were participatory observation, in-depth interviews, group discussions, and document studies. The results showed that Kedamean Sub-district has extensive home garden potential but has not been optimally utilized. Participatory extension strategies and intensive assistance have proven effective in increasing the participation, knowledge, and skills of women farmer group members in home garden management. This program has a positive impact on food availability, consumption quality, household income, and strengthening social capital. Synergy between stakeholders is needed to optimize home gardens as a source of family food and income.